Validity and reliability of anthropometric equations versus dual X-ray absorptiometry to estimate body composition in athletes with unilateral lower-limb amputation: a pilot study - Rivera-Amézquita, L. V.; Saavedra-Bernal, X.; Diaz-Moreno, S.; Tordecilla-Sanders, A.; Escorcia-Gomez, D. C.; Ramos-Caballero, D. M.; Svoboda, Z. (PLOS ONE, 2025)
Background Accurate assessment of body composition is essential for monitoring health and performance in high-performance athletes. While anthropometric equations are widely used in conventional sports, their validity in athletes with unilateral lower-limb amputation remains unclear due to assumptions of symmetrical fat and muscle distribution. This study aimed to assess the concurrent validity and reliability of anthropometric equations for estimating body composition in this population, using Dual-energy X-ray Absorptiometry (DEXA) as the reference method.